Keanekaragaman Serangga Penyerbuk Pada Perkebunan Stroberi (Fragaria sp.) di Desa Tongkoh Kecamatan Dolat Raya Kabupaten Karo Sumatera Utara - Fanisah Labibah; Melfa Aisyah Hutasuhut; Zahratul Idami; Fatiani Manik (Jurnal Biologi dan Pembelajarannya (JB&P), 2023)
Pollinating insects are insects that have an important role as intermediaries for pollinating plants by collecting pollen and nectar found in strawberry flowers (Fragaria sp.). This research was conducted to determine the types of pollinating insects and the diversity of pollinating insects. This research was conducted in Tongkoh Village, Dolat Raya Sub District, Karo District, North Sumatra. Intake of pollinating insects is done by observation method. The results of the study obtained 3 orders and 7 families as well as 11 types of pollinating insects with a total of 147 individuals. The most common type of insect found was Apis cerana. The diversity index of pollinating insects was moderate with an H' value of 2.15. This indicated that the diversity of pollinating insects at the study site was in a stable condition because there were no pollinating insect species that were too dominant.